Enhancing takaful penetration in Malaysia: between challenges and innovative strategies - Mahmad Robbi, Ahmad Akram; Muhammad Zuki, Mohd Faizuddin; Gultekin, Dogan Delil (Karya Ilham Publishing, 2025)
This paper examines the penetration challenges faced by the takaful operators in Malaysia, highlighting its limited growth within the Islamic financial sector. While the focus of the study is identifying key barriers, it explores innovative enhancement strategies. By conducting a comprehensive literature review derived from different sources, including government policies, financial reporting, books, journals and magazines, this study finds the need to construct innovative strategies for the takaful operators and other stakeholders to boosting takaful market penetration, aligning with the mission of Malaysia Takaful Association (MTA) to obtain 40 per cent of market penetration by 2030. This study contributes valuable insights to Islamic finance literature and provides practical recommendations for policymakers, takaful operators, and industry associations seeking to enhance Malaysia’s position as a leading takaful market while better serving the diverse protection needs of its population through innovative, accessible solutions